Analisis Kesalahan Berbahasa Tataran Morfologi Dalam Teks Berita Online Pada Website Ganto.Co - Karina, Leni; Putri, Isya Parmai; Damayanti, Elfa; Prawira, Widya Tristiyanti; Aulia, Faiza; Afnita, Afnita (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF MORPHOLOGICAL LANGUAGE ERRORS IN ONLINE NEWS TEXTS ON THE GANTO.CO WEBSITE This study aims to analyze morphological language errors in news texts from the Ganto.co portal. The method used was descriptive qualitative, using listening, recording, and documentation techniques for news texts published between September 20–30, 2025. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusions. The results indicate that the morphological errors found include affixation, reduplication, composition, and the absorption of foreign terms that have not been adapted to Indonesian language rules. Contributing factors include the influence of foreign languages, a lack of understanding of morphological rules, and the habit of using non-standard forms in online news writing. The conclusion of this study suggests that media students, such as those from Ganto.co, need to increase their linguistic awareness to become role models for the proper application of Indonesian in journalistic media.